Parkinsonismo experimental induzido por rotenona em ratos: um estudo temporal de alterações motoras e não motoras e mecanismos envolvidos - Nascimento, Tyciane de Souza (2020)
Parkinson's disease (PD) affects about 1.6% of the world's population over 65 years old, being the second most common neurodegenerative disease in the elderly. PD is characterized by the progressive loss of dopaminergic neurons of the substantia nigra, leading to a severe reduction of dopamine levels, resulting in several motor symptoms (resting tremor, bradykinesia, instability, postural abnormalities and akinesia) and non-motor symptoms (anosmia, depression, dementia, anxiety and constipation). Rotenone is a pesticide that mimics PD symptoms, representing a model of construct criteria. The aim of the present study was to establish a timeline and mechanisms involved in motor and non-motor changes in the experimental model of parkinsonism induced by rotenone in rats. Wistar rats (220-250g) were divided into two groups: ROT (receiving rotenone 2.75mg /kg, i.p. for 21 days) and CTL (receiving the DMSO vehicle + sunflower oil i.p for 21 days). The results showed that rotenone was able to induce motor deficits significantly (p< 0.05) after 14 and 21 days of administration in the horizontal and vertical exploration and mean velocity of the animals in the open field test, as well as in the postural stability in the rearing behavior test, also observed decrease in motor coordination in the rotarod test. The deficit observed after 21 days in rotarod was responsive to apomorphine, which improved the performance of the animals. Rotenone also induced non-motor deficits such as olfactory impairment in the pellet test buried after 7 and 21, as well as in the olfactory discrimination test after 21, type depressive behavior in the sucrose preference test after 14 and 21 days, as well as in working memory in the Y-maze test and aversive memory in the passive avoidance test after the 21st day. Rotenone also significantly delayed gastric emptying of liquids (p< 0.05) and induced the loss of dopaminergic neurons in the striatum and substantia nigra, decreased content of dopamine and DOPAC, microgliosis and astrogliosis in the striatum, in addition to causing oxidative stress in the olfactory bulb and midbrain. We conclude that rotenone causes neurodegeneration and motor and non-motor alterations by mechanisms that involve inflammation and oxidative stress in a timeline that can be similar to the disease clinic, thus being a good model of parkinsonism that can be used in the search for new neuroprotective substances as well as in understanding of the pathogenesis of this disease